PENGUATAN SINYAL GLOBAL SYSTEM FOR MOBILE COMMUNICATION (GSM) MENGGUNAKAN ANTENA YAGI 14 ELEMEN - Firdaus firdaus; Ratna Dewi; Rikki Vitria; Lifwarda lifwarda (Elektron : Jurnal Ilmiah, 2012)
The hand phone provides an easy to communicate in domestic calls or international calls. The radiation pattern of yagi antenna leads to one direction. Therefore, this antenna is selected for signal amplifier in global system of mobile communication. The design of 14 element yagi antenna which applied for signal amplification in the cell phones was conducted in this study. The design was done manually without computer software. The antenna was created using an aluminum pipe in 3/8 inch diameter for element and an aluminum beam for boom. The result showed that the operating frequency between the designed antenna and manufactured antenna are the same i.e. 947 MHz. The bandwidth of yagi antenna is 9 MHz. Moreover, the antenna gain which measured in folded antenna transmitter and BTS transmitter are 16 dB and 12 dB respectively. That result is caused differences in distance at the measurement time. Utilization of yagi antenna has succeeded to increase signal amplification in hand phone